Merchandising at the point of sale: differential effect of end of aisle and islands - Álvaro Garrido-Morgado; Óscar González-Benito (BRQ Business Research Quarterly, 2015)
Summary Merchandising at point of sale comprises a set of techniques aimed at encouraging the purchase at the point of sale. This paper analyzes the impact on sales of two of these techniques, especially used in the context of non-specialized food stores and rarely distinguished in academic research: (1) the presentation of product in the ends of the aisles or main aisles, leading from the side aisle access and, (2) the presentation of the product in islands within the main aisles. This research combines cross-sectional and longitudinal data and analyzes specific information on sales and commercial stimulus for all references in two large categories of products from a hypermarket over ten weeks. Results show that both the ends of aisle and the islands have a positive effect on sales and their relative importance depends on the nature of the category analyzed. There are also greater synergies between ends of aisle and price promotions. Finally, the results provide some evidence into the impact of the extension or termination of these merchandising stimuli."
Keywords: 650; Retail; Merchandising; End of aisle and island